Hubungan Antara Terpaan Promosi Penjualan dan Tingkat Kepercayaan dengan Keputusan Pembelian Produk Bean Spot - Uci Andriani; Tandiyo Pradekso; Wiwid Noor Rakhmad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Companies carry out various strategies to survive in the midst of business competition. Bean Spot carries out a sales promotion strategy to increase sales. Bean Spot also builds consumer trust through social media. However, with all the efforts that have been made, Bean Spot was unable to achieve the sales target. This study aims to explain the correlation between sales promotion exposure and the level of trust with purchase decision of Bean Spot products. Sales Promotion Stimulus Theory and Brand Equity Theory are used in this study to explain the correlation between variables. The sample of this research is 100 respondents aged 18 -35 years old in Palembang City who have seen Bean Spot sales promotions through print and social media, and have purchased Bean Spot products at least once. Through the Kendal Tau-B correlation analysis technique, the results of the first hypothesis test show that there is no correlation between sales promotion exposure and the decision to purchase Bean Spot products as evidenced by a significance value of 0.275. Then the second hypothesis test shows that there is a correlation between the level of trust and the decision to purchase Bean Spot products with a significance value of 0.000 and a coefficient value of 0.353.